The Effect of Cover Cropping on Maize Production: A Case Study Bishop Barham University Gardens in Kabale District - Gilbert Birungi (Uganda Christian University, 2025)
The purpose of this study was to assess the effects of cover cropping on maize production at in Kabale District. The research was guided by the following objectives; to identify the effects of cover cropping on maize production in kabale district, to assess farmers' perceptions and knowledge of cover cropping practices and to propose strategies for promoting cover cropping as a sustainable agricultural practice for maize production. The experiment employed a Randomized Complete Block Design (RCBD) to assess the effect of cover cropping on maize growth and yield. The study area was demarcated into plots measuring 6mx4m. These were further subdivided into blocks of 3MX2M, each receiving specific treatments. The treatments consisted of two cropping systems: maize grown with a cover crop (intercropped with beans) and maize grown as a sole crop (monoculture). In conclusion, Legume cover crops (e.g beans ) significantly improved maize germination, plant height, leaf area, stem girth, biomass, and yield compared to the control and grass cover crops, Mixed cover cropping had the highest yield performance, soil moisture retention, and organic matter levels while also demonstrating superior weed suppression. The study found out that most farmers were aware (68%) of cover cropping, with 74% believing it improves soil health. However, only 35% currently practice it, largely due to seed inaccessibility (46%). Strategies like media sensitization (60%), farmer training (55%), and integration into extension services (47%) have shown promise but require scaling and better coordination. Based on the findings: Cover cropping, particularly with legumes and mixed species, significantly enhances maize performance in terms of growth, yield, and soil health. Farmers are willing and partially informed, but adoption is limited by logistical challenges such as lack of training and seed access. Based on the conclusions drawn from this study, the following recommendations are made: Farmers in Kabale and similar agroecological zones should be encouraged to adopt cover cropping practices, such as intercropping maize with legumes (e.g., beans), to improve land use efficiency and economic returns. Further long-term studies should be conducted to evaluate the impacts of cover cropping on soil fertility, pest control, erosion prevention, and climate resilience, as well as overall sustainability across multiple cropping seasons.